A ensaística especular e fantasmática de Ítalo Calvino - Miranda, Igor Gonçalves (2021)
This text results from the research whose general objective is to reveal the specular and ghostly images of the writer Italo Calvino. These images are revealed from a selection of textual and paratextual essays that reflect, in the past and in the future, the meaning of his literary experience. A play of images is built from the fragmentation of a more homogeneous set of texts, published between the 1950s and 1980s: the collections of essays Assunto encerrado (2006), Seis propostas para o próximo milênio (1999), Mundo escrito e mundo não escrito (2015), the prefaces to the second edition of A trilha dos ninhos de aranha (2004) and the gathering of fantastic novels Os nossos antepassados (2014), moreover the postfaces to O castelo dos destinos cruzados (2001) and Se um viajante numa noite de inverno (1999), henceforth considered small critical essays. This approach traces specularity and phantasmagoria in the discourse, aspects that bring together the heterogeneity of texts from the same perspective. To achieve this purpose, a theoretical study about the essay genre as a poetics of the images of subjectivity is accomplished and presented. The authors of the essay theory are Montaigne (2016), Lukács (2018), Bense (2018), Adorno (2003), Starobinski (2018), Aira (2018). For the study of paratextuality and the calvinian editorial movement, it is considered Genette (2009), Barenghi (2002), Klein (2013) e Troiano (2015). The authors who explain the theory of the writing of the self (self-portrait, self-fiction and autobiography) and specularity (mirror image and mise en abyme) are James Hall (2014), Beaujour (1980), Lejeune (2014), Colonna (2014), Gide (2013), Valentina and Dällenbach (1975), Eco (1989), Hutcheon (1980) e Waugh (1984). The phantom theory was divided into two moments: the first involves aspects of the khorology of memory and phantasmatic hantology based on the Henri Bergson’s philosophy of memory (1988; 2006a; 2006b) and his interpreters Paiva (2005) and Fujita (2009); the second deals with the collective dimension of the phantom, whose authors are: Derrida (1994) e Guerreiro (2011). In Italo Calvino’s literary experience, essay and fiction are inseparable and, therefore, his specular self-image shines both in one and in the other. The different profiles of the “Calvino writer” are mirrored in the essays based on the text and the editorial movement, i.e., the “Calvino editor”, produces the ghostly images that chase and compress the past and the future: these are images of subjectivity dynamized in time. The interest of this research resides in this self-reflective game. The relationship the writer maintains with the images of himself is phantasmatic, that is, it is not conciliatory, however, it always drives him towards the creation and reception of new texts that challenge him, a fact that allowed to observe the process of his literary maturation.